2008
DOI: 10.1016/j.jpainsymman.2007.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care Integration Project (PCIP) Quality Improvement Strategy Evaluation

Abstract: This study evaluated the effectiveness of implementation of common assessment tools, collaborative care plans, and symptom management guidelines for cancer patients as a strategy to improve the quality, coordination, and integration of palliative care service across organizations and health care sectors. A pre-post design to measure the impact on symptom management, caregiver burden and satisfaction with care delivery, and service utilization was used. Two cohorts of eligible patients and caregivers completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
2
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 4 publications
3
31
2
2
Order By: Relevance
“…The province-wide initiative to standardize symptom and performance status assessments was modeled on a successful pilot project, 9,10 which suggested that routine use of these tools decreased emergency department visits, hospital admissions, and in-hospital deaths. 10 Details of the nature of the provincial initiative have been described elsewhere.…”
Section: Data Sources and Collectionmentioning
confidence: 99%
See 3 more Smart Citations
“…The province-wide initiative to standardize symptom and performance status assessments was modeled on a successful pilot project, 9,10 which suggested that routine use of these tools decreased emergency department visits, hospital admissions, and in-hospital deaths. 10 Details of the nature of the provincial initiative have been described elsewhere.…”
Section: Data Sources and Collectionmentioning
confidence: 99%
“…The province-wide initiative to standardize symptom and performance status assessments was modeled on a successful pilot project, 9,10 which suggested that routine use of these tools decreased emergency department visits, hospital admissions, and in-hospital deaths. 10 Details of the nature of the provincial initiative have been described elsewhere. 9,10 Briefly, the initiative's goal is to improve symptom management and collaborative palliative care planning through earlier identification, documentation, and communication of patients' symptoms and performance status.…”
Section: Data Sources and Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Entre los s铆ntomas que pueden incrementar la carga de los cuidadores se encuentran alteraciones de la memoria, que se present贸 en 38%; alteraciones en la independencia para realizar las actividades b谩si-cas cotidianas en 29%, y de la vida diaria 21,2%; trastornos del sue帽o en 16%, y alteraciones comportamentales en 15%. Futuros estudios deber铆an medir la carga del cuidado con instrumentos validados en nuestro idioma para conocer el impacto de los programas multidisciplinarios en la atenci贸n de estos pacientes, como ha sido reportado en otras lenguas (36,37). Este aspecto proporciona nuevas perspectivas para estudiar en el futuro en relaci贸n con el cuidado paliativo y la rehabilitaci贸n en pacientes no oncol贸gicos.…”
Section: El Estudiounclassified